Web-of-Objects Based User-Centric Semantic Service Composition Methodology in the Internet of Things. (8th May 2014) - Ara, Safina Showkat; Shamszaman, Zia Ush; Chong, Ilyoung
The general goal of the Web-of-Objects (WoO) is to simplify object and application deployment, maintenance, and operation of IoT infrastructures. WoO also aim to provide user-centric IoT service by enabling object virtualization and semantic ontology based service composition. In WoO, semantic modeling of objects plays a distinguished role in achieving interoperability of device and service through semantic ontology model. In this paper, we propose a semantic functional module for user centric service composition in WoO platform. We design an ontology model for virtual object (ViO); it is the physical representation of real world objects. Consequently, we present a user-demand based service composition by showing an use case of WoO. In the proposed semantic based service composition approach, virtual object and composite virtual object are the key entity; this class of objects allows composing services from heterogeneous objects by following a service composition algorithm. This algorithm creates composite service along with the semantic description of that service. The proposed approach of service composition enhances the collaboration of objects as well as services. In the proposed system, user can search a service using natural language through the user interface; on the other hand, the service composition module creates the service by selecting the required objects dynamically.